2013
DOI: 10.4028/www.scientific.net/aef.8-9.445
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Brush Cutters Vibrations on Human Body

Abstract: Abstract. In recent years there have been many cases of HAVS being reported for people who work in agriculture, horticulture, landscape gardening and forestry. The work described in this paper assesses the transmitted vibration to the human body from a hand guided power tool, means a brushcutter. As it is known the brushcutters induce a high level of vibrations on human operators. Depending by brushcutter's type, exposure time and human subjectivity, we can discuss about the vibration influence on human body. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Based on these conditions, we investigated the interaction between the AHE's vibrations and working postures on agricultural operators. Prolonged and excessive WBV or HAV are associated with various occupational health disorders, mainly concerning hands, arms, and spine [ 28 , 29 ]. Our results showed that the brushcutter is the AHE that induces higher stress in sEMG activity and vibration stress.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these conditions, we investigated the interaction between the AHE's vibrations and working postures on agricultural operators. Prolonged and excessive WBV or HAV are associated with various occupational health disorders, mainly concerning hands, arms, and spine [ 28 , 29 ]. Our results showed that the brushcutter is the AHE that induces higher stress in sEMG activity and vibration stress.…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptoms are: hearing loss, stress, irritation, memory loss and sleep disturbance (Nelson et al 2005, Ouis 1999, Shah et al 2018, Stansfeld et al 2000, Tengku et al 2013. Long-term exposure to vibrations may also have negative health effects in the form of vascular, neurological and musculoskeletal disorders (Dziurdź 2011, Ko et al 2011, Pettersson 2013, Truţa et al 2013. Various aspects of working with a brush cutter have been researched by many authors; however, the issue of noise level emitted by different cutting attachments while tending forest plantations has not been assessed yet.…”
Section: Introductionmentioning
confidence: 99%